Environmental Correlates of Bronchial Asthma in Children in a Slum of Meerut - A Cross-Sectional Study - Elizabeth George, Carolin; Chopra, H; Garg, S. K.; Bano, Tanveer; Jain, Seema; Kumar, Arun (International Journal of Medical Research and Review, 2014)
Introduction: In India, an estimated 57,000 deaths were attributed to Asthma in 2004 & it was seen as one of the leading cause of morbidity and mortality (WHO 2004). The range of prevalence of Bronchial asthma in children in India varied from 2% to 20%. So far, no community based studies have been conducted in Western Uttar Pradesh to find out the prevalence of bronchial asthma in children. The present study is an effort in that direction. Objective: To determine the prevalence of bronchial asthma among children of 5 – 15 years and its environmental determinants. Methods: A cross sectional community based study was conducted by interviewing the parents of randomly selected children in the age group of 5– 15 years using International Study on Allergy And Asthma In Childhood (ISAAC) Questionnaire. Assuming the prevalence of bronchial asthma to be 10% at 95% confidence interval and allowing a relative precision of 20% for the estimate and expecting a non response rate of 5 %, the sample size was calculated as 907. The observations thus obtained were tabulated and analysed using relevant statistical methods. Results: A total of 880 children of 5– 15 yrs participated in the study showing a response rate of 97.02%. The prevalence of asthma was found to be 9.3%. The prevalence of asthma was found to be associated with inadequate ventilation (OR=2.71) and presence of pets (OR= 2.70). Conclusion: The prevalence of asthma was found to be 9.3% and it warrants a national program to reduce the morbidity in children.